Let $X_{1}, \dots, X_{n}$ be i.i.d. having the exponential distribution $Exp\left(0, \theta_{x}\right)$ with $\theta_{x}>0$, and $Y_{1}, \dots, Y_{n}$ be i.i.d. having the exponential distribution $Exp\left(0,\theta_{y}\right)$ with $\theta_{y}>0$. Assume that $X_{i}$'s and $Y_{j}$'s are independent, but they are unobservable.

Suppose that our sample is $\left(Z_{1}, \Delta_{1}\right), \dots,\left(Z_{n}, \Delta_{n}\right)$, where $Z_{i}= X_{i}(1-\Delta_{i}) + Y_{i}\Delta_{i}$ and $\Delta_{i}=I(X_i \ge Y_i)$ for $i=1, \dots, n$. Please find an unbiased estimator and the UMVUE of $\theta_{x}-\theta_{y}$.

Note that the probability density function (p.d.f.) of $Exp(a,\theta)$ is $\theta^{-1}e^{-(x-a)/\theta}I(x>a)$.

The parameter, $\theta$, is commonly called the MTBF (mean time between failures) or MTTF (mean time to fix). The inverse of the parameter, $1/\theta$, is equal to the hazard rate.

This question is a part of Exercise 3.9 in Shao Jun (2003).

The following is my attempt.

Here is the skeleton of my solution. We first find the complete and sufficient statistics $T$, and then try to construct the unbiased estimator $\widehat{S}$, then the UMVUE would be $\mathbb{E}[\widehat{S}\vert T]$.

Let $U_i = X_i - Y_i$. When $u\le 0$, we have \begin{align*} P(U_i \le u) & = P(X_i- Y_i \le u) \\ & = \int_{0}^{\infty} \int_{x-u}^{\infty} \frac{1}{\theta_x\theta_y} \exp\left\{ -\frac{x}{\theta_x} -\frac{y}{\theta_y} \right\} d y d x \\ & = \exp (u / \theta_y) \frac{\theta_y}{\theta_x + \theta_y} . \end{align*} This implies $P(\Delta_i = 1) = \frac{\theta_x}{\theta_x + \theta_y}$. Further, \begin{align*} P ( Z_i \le z, \Delta_i = 1 ) & = \frac{\theta_x}{\theta_x + \theta_y} - \frac{\theta_x}{\theta_x + \theta_y} \exp \left( - \frac{\theta_x + \theta_y}{\theta_x \theta_y} z\right) \triangleq P_{1,i} , \\ % & = P ( Z_i \le z, \Delta_i = 0 ) & = \frac{\theta_y}{\theta_x + \theta_y} - \frac{\theta_y}{\theta_x + \theta_y} \exp \left( - \frac{\theta_x + \theta_y}{\theta_x \theta_y} z\right) \triangleq P_{0,i} . \end{align*} Then $Z_i$ and $\Delta_i$ are independent, $Z_i\sim E\left(0, \frac{\theta_x\theta_y}{\theta_x+\theta_y}\right)$, and $P_{Z_i,\Delta_i} (z,\delta) = P_{1,i}^{\delta} P_{0,i}^{1-\delta}$.

Notice that the p.d.f. of the joint distribution of $Z_i$'s and $\Delta_i$'s is given by \begin{align*} & p\left( Z_1 = z_1, \dots, Z_n = z_n, \Delta_1 = \delta_1, \dots, \Delta_n = \delta_n \right) \\ & = \prod_{i=1}^n \left[ \frac{\theta_x + \theta_y}{\theta_x \theta_y} \exp\left( - \frac{\theta_x + \theta_y}{\theta_x \theta_y} z_i \right) \left\{ \frac{\theta_x}{\theta_x + \theta_y} I (\delta_i = 1) + \frac{\theta_y}{\theta_x + \theta_y} I (\delta_i = 0)\right\} \right] I(z_i>0)\\ & = \left(\frac{\theta_x + \theta_y}{\theta_x \theta_y}\right)^{n} \exp\left( - \frac{\theta_x + \theta_y}{\theta_x \theta_y} \sum_{i=1}^n z_i \right) \left( \frac{\theta_x}{\theta_x + \theta_y} \right)^{\sum_{i=1}^n \delta_i} \left( \frac{\theta_y}{\theta_x + \theta_y} \right)^{n- \sum_{i=1}^n \delta_i} I(z_{(1)}>0) \\ & = \exp\left( - \frac{\theta_x + \theta_y}{\theta_x \theta_y} \sum_{i=1}^n z_i \right) \theta_x^{-n+\sum_{i=1}^n \delta_i} \theta_y^{- \sum_{i=1}^n \delta_i} I(z_{(1)}>0) \end{align*} Therefore, the joint distribution of $Z_i$'s and $\Delta_i$'s is from an exponential family with $T = (\sum_{i=1}^n \Delta_i, \sum_{i=1}^n Z_i)$ as the complete and sufficient statistic.

I don't know how to continue and if it will actually exist. Thanks for any suggestions and answers.


Thanks for the suggestion from @Xi'an.

If we are interested in $1/\theta_x - 1/\theta_y$, we could construct an unbiased estimator according to $\frac{n-1}{n} \mathbb{E} \frac{\sum_{i=1}^n (1-\Delta_i)}{\sum_{i=1} Z_i} - \frac{n-1}{n} \mathbb{E} \frac{\sum_{i=1}^n \Delta_i}{\sum_{i=1} Z_i} = 1/\theta_x - 1/\theta_y$.

But in this question, we focus on $\theta_x -\theta_y$ Although $\mathbb{E}[X_i] = \theta_x$, we have $\mathbb{E}[X_i \vert Z_i,\Delta_i]$ is a function of $\theta_x$, $Z_i$ and $\Delta_i$. However, $\mathbb{E}[X_i \vert Z_i,\Delta_i]$ is non-linear in terms of $\theta_x$. So, I don't know how to continue.

  • 2
    $\begingroup$ In effect, you observe an iid sample $(Z_i)$ of an exponential distribution with (rate) parameter $1/\theta=1/\theta_x+1/\theta_y.$ Since $\theta$ is a symmetric function of the parameters, if you could find an unbiased estimator of $\theta_x-\theta_y$ it would necessarily also be an unbiased estimator of $\theta_y-\theta_x,$ immediately implying $\theta_x=\theta_y.$ Since you don't assume equality of the parameters, your objective is hopeless: such an unbiased estimator doesn't exist. $\endgroup$
    – whuber
    Commented Mar 20, 2022 at 13:59
  • $\begingroup$ @whuber Thanks a lot! Yes, parameter of $Z$, i.e., $\theta$ is a symmetric function of the parameters $\theta_x$ and $\theta_y$. But, I think, it may not be sufficient to show that the unbiased estimator doesn't exist. Because, $\Delta$ contains the information of $I(\theta_x \ge \theta_y)$. $\endgroup$
    – Huihang
    Commented Mar 20, 2022 at 14:18
  • 2
    $\begingroup$ Thank you--I thought I might be overlooking something. So that means you should be able to use the mean of the $\Delta_i$ to estimate the chance with which one distribution will exceed the other--and that ought to lead to an effective strategy for estimating another function of $(\theta_x,\theta_y)$ from which you can obtain estimators of both parameters. $\endgroup$
    – whuber
    Commented Mar 20, 2022 at 14:26
  • 1
    $\begingroup$ The fascinating thing is that they are not symmetrical, as shown by my "answer". $\endgroup$
    – Xi'an
    Commented Mar 22, 2022 at 7:21
  • 1
    $\begingroup$ @Xi'an Yes. This question is a part of Exercise 3.9 in Shao Jun (2003). I added the source in my question. $\endgroup$
    – Huihang
    Commented Mar 22, 2022 at 11:09

1 Answer 1


Changing the question in two different ways allows for some answers:

  1. If $\theta_x$ and $\theta_y$ are rate rather than scale parameters, $$ \frac{n-1}{n} \frac{\sum_{i=1}^n (1-\Delta_i)}{\sum_{i=1} Z_i} - \frac{n-1}{n} \frac{\sum_{i=1}^n \Delta_i}{\sum_{i=1} Z_i}\tag{1} $$ is an unbiased estimator of $1/\theta_x - 1/\theta_y$ and since it only depends on $\mathbf T$, it is the UMVUE.

  2. If instead $Z=\max\{X,Y\}$, with $\theta_x$ and $\theta_y$ scale parameters, the conditional distribution of $Z$ conditional on $\Delta=1$. Since $$\mathbb P(\Delta=1)=\frac{\theta_x}{\theta_x+\theta_y}$$ we have \begin{align} \mathbb P(Z\le z|\Delta=1)&=\frac{\theta_x+\theta_y}{\theta_x}\mathbb P(Z\le z,\Delta=1)\\ &=\frac{\theta_x+\theta_y}{\theta_x}\mathbb P(X\le z,X>Y)\\ &=\frac{\theta_x+\theta_y}{\theta_x}\int_0^z\int_0^x \frac1{\theta_x\theta_y} \exp\{-x/\theta_x-y/\theta_y\}\text dx\text dy\\ &=\frac{\theta_x+\theta_y}{\theta_x}\int_0^z(1-\exp\{-x/\theta_y\})\frac{\exp\{-x/\theta_x\}}{\theta_x}\text dx\\ &=\frac{\theta_x+\theta_y}{\theta_x}[1-\exp\{-z/\theta_x\}]-\\ &\qquad\frac{\theta_x+\theta_y}{\theta_x}(\theta_x^{-1}+\theta_y^{-1})^{-1} [1-\exp\{-z(\theta_x^{-1}+\theta_y^{-1})\}]\\ &=\frac{\theta_x+\theta_y}{\theta_x}[1-\exp\{-z/\theta_x\}]- \frac{\theta_y}{\theta_x}[1-\exp\{-z(\theta_x+\theta_y)/\theta_x\theta_y\}] \end{align} This is a signed mixture of two Exponential distributions $$\frac{\theta_x+\theta_y}{\theta_x}\mathcal Exp(\theta_x)-\frac{\theta_y}{\theta_x}\mathcal Exp(\theta_x\theta_y/(\theta_x+\theta_y))$$ which is illustrated by the fit in the following graphs:

enter image description here

based on $n=10^6$ simulations from $\mathcal Exp(10)$ and $\mathcal Exp(1/10)$ samples. This distribution has mean \begin{align}\mathbb E[Z\le z|\Delta=1] &=\frac{\theta_x+\theta_y}{\theta_x}\theta_x-\frac{\theta_y}{\theta_x}\frac{\theta_x\theta_y}{\theta_x+\theta_y}\\ &=\theta_x+\theta_y\left[1-\frac{\theta_y}{\theta_x+\theta_y}\right]\\ &=\theta_x+\frac{\theta_y\theta_y}{\theta_x+\theta_y}\end{align} The second term above is symmetric in $(\theta_x,\theta_y)$. Therefore, $$\mathbb E[Z\le z|\Delta=1]-\mathbb E[Z\le z|\Delta=0]=\theta_x-\theta_y$$ which leads immediately to an unbiased estimator based on $(\mathbf X,\boldsymbol \Delta)$: $$\dfrac{\sum_{i=1}^n Z_i\Delta_i}{\sum_{i=1}^n\Delta_i}- \dfrac{\sum_{i=1}^n Z_i\{1-\Delta_i\}}{\sum_{i=1}^n\{1-\Delta_i\}}\tag{2}$$ although I cannot tell about about (2) being UMVUE as the $Z_i$'s are not from an exponential family.

  • 1
    $\begingroup$ Thank you very much for your serious reply. This is very useful. I think this answer temporarily ends my question until there is a clearer conclusion, for example, some negative proofs show that the unbiased estimation does not exist. $\endgroup$
    – Huihang
    Commented Mar 23, 2022 at 4:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.